Pameran Budaya Lokal Sebagai Pelestarian Budaya Dalam Meningkatkan Kesadaran Masyarakat Kepulauan Riau - Ferdi, Ferdi; Sevriyansah , Toni; Riyadi , Ahmad (CV. ITTC INDONESIA, 2023)
The Community in Culture is an agency that is a community within society which has an important role in maintaining and protecting cultural diversity, local wisdom, and forming local arts in the Riau Islands. Apart from that, we also want to know what are the inhibiting factors in maintaining local culture and the factors that support the implementation of local culture preservation by the cultural service. This research is descriptive research with qualitative research methods, namely collecting data from interviews with participants and also documentation. The results used in this research have an important aim for the cultural community in increasing cultural diversity in the Riau Islands by holding cultural festivals, namely increasing the potential of local culture by inviting people to see cultural heritage exhibitions in the Riau Islands, which aims to provide useful experiences and insights. more to the community and increase public awareness of the importance of local culture which must be preserved.